ORIGEM DAS LÍNGUAS EM VICO, HERDER E ROUSSEAU (Polifonia, 1994)
ABSTRACT: This paper discusses the issue of the origin of language of three philosophers: Vico, Herder and Rousseau. Although al three share the thesis that language has a natural origin, they diverge considerably among themselves. the focus of this study is the differences among the three.